2013
DOI: 10.4236/mi.2013.21003
|View full text |Cite
|
Sign up to set email alerts
|

Gate Lip Hydraulics under Sluice Gate

Abstract: This paper present the effect of the lower gate lip on the coefficient of contraction, velocity and discharge which have been made in a rectangular flume with four gates opening from (2 to 4.5) cm, five different discharges from (6.2 to 18.15) l/s and five different gate cases (vertical and inclined vertically) by angle (45)˚ with and opposite flow direction with horizontal and sharp lower lip. The values of coefficients of contraction (C c) and discharge (C d) increases when gate slope increases with flow dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The value of the discharge coefficient (Cd) decreases by increasing the water level at the upstream of the gate, where it was the lowest possible at the level (35) cm, and the highest possible at the level (15) cm, because lowering the water level upstream of the gate means less discharge passing through it, thus increasing the value of the discharge coefficient (Cd) and vice versa, as in Figure 15) cm, because at the high depths, the discharge is high as well as the average velocity is high and Fr1 is high too and therefore a lower value for (Cc) as shown in Figure (6).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The value of the discharge coefficient (Cd) decreases by increasing the water level at the upstream of the gate, where it was the lowest possible at the level (35) cm, and the highest possible at the level (15) cm, because lowering the water level upstream of the gate means less discharge passing through it, thus increasing the value of the discharge coefficient (Cd) and vice versa, as in Figure 15) cm, because at the high depths, the discharge is high as well as the average velocity is high and Fr1 is high too and therefore a lower value for (Cc) as shown in Figure (6).…”
Section: Resultsmentioning
confidence: 98%
“…Whereas, the nonlinear equation performed better than the linear equation. Mohammad and Khalil [6] tested the effect of five states on the level of the lower edge of one-open gate and the angle of the gate slope on contraction, discharge, and velocity coefficients, for different discharges and a variable gate opening, they concluded that the value of both contraction coefficient (Cc) and discharge coefficient (Cd) increase with increasing slope of the gate towards the direction of flow and at the horizontal edge level, and it decreased with the slope of the gate against the flow direction with horizontal plane of the lower edge. The study showed that velocity coefficient (Cv) was not affected and its value remained constant.…”
Section: Introductionmentioning
confidence: 99%
“…(9&10) shows that the value of discharge coefficient Cd decreases with the increase of , and its value increases with the increase distance between baffles. Comparing figure (9) with figure (10) it can be noted that the channel slope has a negative effect on the value of Cd which shows less values of discharge coefficient Cd for the same geometric combinations.…”
Section: Variation Of (Cd) With the Ratiomentioning
confidence: 90%
“…Lin, et al, (2002) presents a theoretical formula and some experimental graphs to determine maximum allowable tail water depth for free flow (or minimum allowable tail water depth for submerged flow). The effect of lower gate edge on water surface profile has been studied in rectangular flume by (Mohammed & Khaleel, 2013).The discharge coefficient for the free flow through three baffle sluice gates in horizontal and inclined channel was investigated in this study.…”
Section: -Submerged Flow Condition (mentioning
confidence: 99%
“…Berdasarkan hal di atas, maka salah satu alternatif yang dapat dilakukan adalah pembangunan suatu bendung gerak sebagai pengendali banjir tampungan air di musim hujan dan dapat digunakan secara efisien di musim kemarau (Kamiana, 2011). Tersedianya bangunan Bendung Gerak Radial Gate Sungai Parit tersebut diharapkan dapat mengurangi bencana banjir di wilayah Kecamatan Kawunganten dan sekitarnya, serta secara tidak langsung akan meningkatkan taraf hidup masyarakat setempat (Mohammed, Y., Khaleel, & S, 2013).…”
Section: Gambar 1 Peta Lokasi Penelitian Bendung Gerak Ujungmanik (Go...unclassified